What is the prime factorization of 625?

5 x 5 x 5 x 5= 625
5 x 5= 25 x 5=125 x 5 = 625

Expert answered|WeeCHEN|Points 6755|

Question

Asked 1/14/2015 9:28:09 PM

Updated 1/14/2015 9:50:10 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Rating

There are no new answers.

If four times a number plus 3 is 11, what is the number? User: Given the formula D = ABC, what is the formula for C? User: Solve this equation: y/9 + 5 = 0 User: Solve this inequality: 8z + 3 – 2z User: Simplify the following expression: 35 + (–13) + (+8) – (–6). User: Solve this equation: –9h – 6 + 12h + 40 = 22. **Weegy:** 9h ? 6 + 12h + 40 = 22;
3h + 34 = 22;
3h = 22 - 34;
3h = -12;
h = -12/3;
h = -4 The correct answer is A. h = -4 **User:** Solve this equation: 2s + s + 12 = 132. **Weegy:** 2s+s+12=132
3s=132-12
s=120/3
s=40 **User:** Find the value of Z in the following equation: 8Z = 64. **User:** Solve this inequality: 3b – 7 **Weegy:** answer is b**User:** Solve this inequality: j/4 – 8 **Weegy:** j/4 ? 8 **User:** Solve this inequality: 3p – 6 > 21. **User:** Solve this inequality: 3q + 11 + 8q > 99. **Weegy:** 3q+11+8q>99 11q + 11 > 99 11q > 99 - 11 11q > 88 q > 8 **User:** Solve this equation: 80 = 3y + 2y + 4 + 1 **Weegy:** 80 = 3y + 2y + 4 + 1 80 = 5y + 5 80 - 5 = 5y -5y = -75 y = 15 **User:** Solve the inequality: 12p + 7 > 139 **User:** Simplify this expression: 13 + (–12) – (–5) = ? **User:** Solve the following equation: 6y – 20 = 2y – 4. **Weegy:** 6y ? 20 = 2y ? 4; 6y - 2y = -4 + 20; 4y = 16; y = 16/4; y = 4 **User:** Simplify this expression: 4p + 9 + (–7p) + 2 = ? **Weegy:** To simplify this expression:
4p 9 ( 7p) 2
Solution:
4p+9+(-7p)+2=?
= 4p-7p+9+2
answer is -3p+11
**User:** Simplify and solve this equation for q: 3q + 5 + 2q – 5 = 65. **Weegy:** 3q + 5 + 2q ? 5 = 65 5q = 65 q = 65/5 q = 13 **User:** Simplify and solve this equation: 4m + 9 + 5m – 12 = 42. **User:** Solve this inequality: 3p – 16 < 20. (More)

Question

Updated 1/17/2015 11:23:45 PM

1 Answer/Comment

y/9 + 5 = 0

y/9 = -5

y = -5*9

y = -45

y/9 = -5

y = -5*9

y = -45

Added 1/17/2015 11:22:28 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [1/18/2015 1:57:59 PM]

31,084,895

questions answered

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

PranaMachine

$80.97

Hearts 1,653 Views 6,405 Streams 87

phpmicro

$50.80

Hearts 1,155 Views 114,753 Streams 107

jezziem

$22.30

Hearts 725 Views 37,427 Streams 39

judymrnd

$21.15

Hearts 529 Views 22,874 Streams 35

sacharyn

$12.15

Hearts 243 Views 10,594 Streams 19

emdjay23

$11.50

Hearts 639 Views 25,311 Streams 47

aeronjosef

$11.10

Hearts 563 Views 14,269 Streams 25

There are no comments.